Increasing haemoglobin level of pregnant women: potential of corn cookies and purple sweet potato cookies - Mutia, Wa Ode Nurul; Alam, Hilda Sulistia; Dahlan, Dahniar (Poltekkes Kemenkes Bandung, 2026)
Background: Iron deficiency anemia is common in pregnant women and can cause premature birth, low birth weight, and labor complications. Corn and purple sweet potatoes are foods rich in iron, folic acid, and antioxidants. Objective: The study aimed to determine the effect of consuming corn cookies and purple sweet potato cookies on increasing hemoglobin levels in pregnant women. Methods: The method used was a quasi-experimental design with a pre-post test only with a control group. After the initial hemoglobin examination (pre-test) in the three groups, an intervention was given: corn cookies and purple sweet potato cookies for 14 days in the intervention group, and a repeat Hb examination in the 3 groups (Post-Test). The study sample was 30 respondents and was analyzed using Kruskal-Wallis. Results: The results showed a statistically significant difference in average hemoglobin (Hb) value after treatment between the three study groups, namely the purple sweet potato cookies group (19.40), the corn cookies group (16.30), and the control group (10.80). The results of the calculation of the nutritional value of corn cookies per serving (100 gr), obtained energy results of 171.2 Kcal, Protein 3.66 g, Fat 11.94 g, carbohydrates 14.26 g, and Iron (Fe) of 1.32 mg while the nutritional value of purple sweet potato cookies per serving (100 gr), shows energy of 180.1 Kcal, protein 3.18 g, fat 12.22 g, carbohydrates 16.14 g, and Iron (Fe) of 1.58 mg. Conclusion: Purple sweet potato cookies and corn cookies have the potential to increase hemoglobin levels in pregnant women.